Transformasi Wereng Batang Cokelat dari ‘Hama Tidak Penting’ Menjadi ‘Hama Elite’ Pada Ekosistem Padi Sawah di Pulau Jawa: Sebuah Pembahasan Etnografi Multispesies - Rhino Ariefiansyah (Antropologi Indonesia, 2018)
This paper aims to situate the transformation Brown Plant-Hopper (BPH) in broader issues of wetland rice socio-agroecosystem management in Java. By considering multispecies ethnography, this paper argues that the transformations of BPH from "unimportant insects" into "elite dangerous pests" is a consequence of the complexity of the interplay between biological processes and social processes in the context of managing biotic and abiotic elements in rice farming ecosystem. In this context, wetland rice ecosystems (sawah) is a unique social and biological space where multi-species actors interact with one another, directly or indirectly. Thus, the transformation of BPH insects is the result of aggregate of events on a different time and spatial scale. It is a continuation of everyday acts, and it is long term consequences, as well as of global and local processes. The data used for this paper obtained through interviews, field observations, and literature studies. During the data collection process, the author interacts with farmers, scientists, government officials, and activists.